Informatics and data science: an overview for the information professional - Cervone, H Frank (Digital library perspectives, 2016)
Purpose - This paper aims to describe the emerging field of data science, its significance in the larger information landscape and some issues that distinguish the problems of data science and informatics from traditional approaches in the information sciences. Design/methodology/approach - Through a general overview of the topic, the author discusses some of the major aspects of how work in the data sciences and informatics differ from traditional library and information science. Findings - Data science and informatics, as emerging fields, are expanding our understanding of how the massive amount of information currently being generated can be collected, managed and used. While these may not be traditional "library" problems, the contributions of the library and information science communities are critical to help address aspects of these issues. Originality/value - The emerging fields of data science and informatics have not been extensively explored from the perspective of the information professional. This paper is designed to help information professionals better understand some of the implications of data science in a changing information environment.